Research on the Electrochemical Properties of Al2−xZnxO3−α. Issue 4 (1st April 2022) - Li, Yang; Ruan, Fei; Bao, Jinxiao; Zhang, Fenglong; Zhang, Yonghe; Gao, Xiong; Song, Xiwen
Abstract : To understand the electrochemical properties of the Al2 O3 based proton conductor in more detail, a solid-state electrolyte Zn-doped Al2 O3 was successfully prepared using the solid-state reaction method at the temperatures of 1873 K for 10 h. The phase structure and microscopic morphology of these materials are thoroughly investigated. The structural analysis results revealed that the electrolyte has a pure perovskite phase structure. The crystal grains are relatively uniform, the ceramic material is dense, and the relative density is greater than 97 percent, according to microscopic morphology analysis. The electrical conductivity of the specimen was measured using the two-terminal AC method to clarify the electrochemical properties of Zn-doped Al2 O3 . The H/D isotope effect of electrical conductivity was studied, and it was discovered that protons are the dominant charge carrier at temperatures ranging from 1073 to 1473 K in hydrogen-rich atmospheres. The electrochemical impedance spectroscopy test showed that in the temperature range of 1073K–1473 K, the conductivity of the sample increases with the increase of temperature, and the electrochemical performance of the sample is the best when the doping amount is x = 0.012. The conductance activation energy ( E a ) is in the range of 1.01–1.62 eV in hydrogen-rich atmospheres. From the point of view of electromotive force measurement, the theoretical (computational) electrical potential matches the measured potential very well. In a hydrogen-rich atmosphere of 1073–1473 K, the proton mobility of Al2− x Zn x O3− α exceeds 0.90. In this work, we proved that Al2− x Zn x O3− α sample is a proton conductor.